Slang Words in Jason Mraz’s Song Lyrics from the Album “We Sing. We Dance. We Steal Things.” - Yusniantari, Ni Luh Dea Indri; Mulyawan, I Wayan; Indriani, Ketut Santi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 31 No 1 (2024): Maret, 2024)
This study entitled “Slang Words in Jason Mraz’s Song Lyrics from the Album We Sing. We Dance. We Steal Things.” aims to identify the types of slang words and analyze the word formation process used in Jason Mraz’s song lyrics. The data used in this study was taken from all song lyrics on Jason Mraz’s album entitled “We Sing. We Dance. We Steal Things.”. The data was collected by using the documentation method. This study used a qualitative method to analyze the data in the form of description using words. There were two theories applied in this study which are the theory proposed by Chapman (2007) to analyze types of slang words and Yule’s theory (2010) to analyze the word formation process. The results of this study indicate there were two types of slang words found in this album, namely primary slang and secondary slang. Primary slang was the most dominant type of slang word because it is commonly used in daily conversation. From the word formation analysis, there were six processes of forming slang found in this album. They are etymology, borrowing, compounding, blending, clipping, and derivation. The most frequent process was blending.